An pasyon ni kristo: devotion and beyond - Ubano-Cid, Rosa C. (San Miguel, Iriga City: University of Saint Anthony, 2013)
An pasyon ni kristo: devotion and beyond.
Includes bibliographical references.
English
Keywords: Devotion